Henrik Schollmayer Lichtenberg, upravnik posestva Snežnik - Kačičnik Gabrič, Alenka (Zgodovina za vse, 1999)
Herik Schollmayer Lichteneger was by education a forester. From 1884 up until his retirement in of 1919, he was employed on the estate of Snežnik - first as manager of the Mašun hunting runs and from 1903 onwards as manager of the entire estate. In addition to his main occupation, Schollmayer Lichtenberg was also interested in a number of other areas, on which he wrote several articles, some which still figure as basic sources for researching individual topics in the fields of historiography, etnology, meteorology and so forth.
Keywords: biografije; gospostvo Snežnik; gozdarstvo; Schoenburg(rodbina); Schollmayer-Lichtenberg, Henrik; upravniki